Development of technology for the process of neutralization of pickling solution of metallurgical production - Lamzina I.V.; Tarasov A.P.; Zheltobryukhov V.F. (Научно-технический вестник Брянского государственного университета)
The leading branch of territorial-production complex of Russia - mechanical engineering. Companies of the industry throw dirt in the form of used organic solvents, toxic compounds of metals with waste galvanic and etching solutions, cutting fluids (coolant) and emulsions. you need to create complex regeneration treatment system of the most valuable components for these liquids. Reset electroplating and etching solutions can lead to the accumulation of heavy metals in the bio-organisms of the coastal zone and to enter them through the food chain to humans. To prevent contamination, a scheme neutralizing acid waste, accompanied by a reduction in the hazard class of the etching solution to IV class with the ability to accommodate long-term storage solid industrial waste in landfills.